Design of the Weight-loss Endoscopy Trial (WET): a multi-center, randomized, controlled trial comparing weight loss in endoscopically implanted duodenal-jejunal bypass liners vs. intragastric balloons vs. a sham procedure - Marcus Hollenbach; Christiane Prettin; Felix Gundling; Wolfgang Schepp; Jochen Seufert; Jürgen Stein; Thomas Rösch; Jens Aberle; Jürgen Feisthammel; David Petroff; Albrecht Hoffmeister (BMC Gastroenterology, 2018)
Abstract Background Obesity is a global problem leading to reduced life expectancy, cardiovascular diseases, diabetes and many types of cancer. Even people willing to accept treatment only achieve a mean weight loss of about 5 kg using commercial weight loss programs. Surgical interventions, e.g. sleeve gastrectomy or gastric bypass are effective but accompanied by risk of serious complications and side effects. Less invasive endoscopic procedures mainly comprise the intragastric balloon (IB) and the duodenal-jejunal bypass liner (DJBL). To date, a randomized comparison between these devices has not been undertaken or shown to be superior to a sham procedure. Methods We designed a multi-center, randomized, patient and assessor-blinded, controlled trial comparing weight loss in endoscopically implanted IB vs. DJBL vs. a sham procedure. A total of 150 patients with a BMI > 35 kg/m2 or > 30 with obesity-related comorbidities and indication for proton pump inhibitors are randomized to receive either IB, DJBL or a sham gastroscopy (2:2:1 ratio). All participants undergo regular dietary consultation. The IB will be removed after 6 months, whereas the DJBL will be explanted after 12 months. All patients will receive gastroscopies at implantation and explantation of the devices or sedation without gastroscopy to maintain blinding. Main exclusion criteria are malignant diseases, peptic ulcer or previous bariatric intervention. Weight loss 12 months after explantation of the devices, changes in comorbidities, quality of life, complication rates and safety will be evaluated. Discussion This trial could help to identify the most effective and safest endoscopic device, thus determining the new standard procedure for endoscopic bariatric treatment. Trial registration 16th January 2017. DRKS00011036. Funded by the German Research Foundation (DFG).